Next Article in Journal
Four Particular Cases of the Fourier Transform
Next Article in Special Issue
Representing Sums of Finite Products of Chebyshev Polynomials of the First Kind and Lucas Polynomials by Chebyshev Polynomials
Previous Article in Journal
Dynamics of the Almost Periodic Discrete Mackey–Glass Model
Previous Article in Special Issue
A Note on the Classical Gauss Sums

Article

# Some Identities Involving Fibonacci Polynomials and Fibonacci Numbers

by 1 and 1,2,*
1
School of Science, Xi’an Technological University, Xi’an 710021, China
2
School of Mathematics, Northwest University, Xi’an 710127, China
*
Author to whom correspondence should be addressed.
Mathematics 2018, 6(12), 334; https://doi.org/10.3390/math6120334
Received: 21 November 2018 / Revised: 15 December 2018 / Accepted: 16 December 2018 / Published: 18 December 2018

## Abstract

The aim of this paper is to research the structural properties of the Fibonacci polynomials and Fibonacci numbers and obtain some identities. To achieve this purpose, we first introduce a new second-order nonlinear recursive sequence. Then, we obtain our main results by using this new sequence, the properties of the power series, and the combinatorial methods.

## 1. Introduction

For any real number x, the Fibonacci polynomials $F n ( x )$ are defined by $F 0 ( x ) = 1$, $F 1 ( x ) = x$, $F 2 ( x ) = x 2 + 1$, $F 3 ( x ) = x 3 + 2 x$, $F 4 ( x ) = x 4 + 3 x 2 + 1$, and the second order linear recursive formula:
$F n + 1 ( x ) = x F n ( x ) + F n − 1 ( x ) , n ≥ 1 .$
If $x = 1$, then $F n ( 1 ) = F n + 1$ is the famous Fibonacci sequence. Its initial values are $F 0 = 0$, $F 1 = 1$, $F 2 = 1$, $F 3 = 2$, $F 4 = 3$, $F 5 = 5$, $F 6 = 8$, $F 7 = 13$, ⋯.
The general expression of $F n ( x )$ is:
$F n ( x ) = 1 x 2 + 4 x + x 2 + 4 2 n + 1 − x − x 2 + 4 2 n + 1 = ∑ k = 0 n 2 ( n − k ) ! k ! · ( n − 2 k ) ! · x n − 2 k , n = 0 , 1 , 2 , ⋯ .$
The generating function of the Fibonacci polynomials $F n ( x )$ is:
$1 1 − x t − t 2 = ∑ n = 0 ∞ F n ( x ) · t n .$
These polynomials play a very important role in the theory and application of mathematics. Because of this, many number theory experts study the properties of $F n ( x )$ and $F n$ and obtain a series of important results. For example, Yuan Yi and Wenpeng Zhang [1] studied the computational problem of the summation:
$∑ a 1 + a 2 + ⋯ + a h + 1 = n F a 1 ( x ) · F a 2 ( x ) ⋯ F a h ( x ) · F a h + 1 ( x ) ,$
where the summation is taken over all $( h + 1 )$-dimension nonnegative integer coordinates $( a 1 , a 2 , ⋯ , a h + 1 )$ such that $a 1 + a 2 + ⋯ + a h + 1 = n$.
They used the elementary and combination methods to give a meaningful identity involving $F n ( x )$ and its derivative $F n ′ ( x )$.
Zhengang Wu and Wenpeng Zhang [2,3] studied the calculation problem of the reciprocal sum of the Fibonacci numbers and Fibonacci polynomials and obtained many interesting identities and calculation formulae.
Other achievements related to Fibonacci numbers and Fibonacci polynomials can also be found in [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]; here, we will not repeat them one by one.
Very recently, Yixue Zhang and Zhuoyu Chen [19] used the elementary method and combination skill to research the calculating problem of one kind sums of the second kind Chebyshev polynomials and then obtained a very interesting identity.
This paper is inspired by [19]. As a note of [1,4], we are going to introduce a new second order non-linear recursive sequence, then use this sequence to acquire a meaningful expression for (2). That is, we shall prove the following:
Theorem 1.
Let h be a positive integer. Then, for any integer $n ≥ 0$, we have the identity:
$∑ a 1 + a 2 + ⋯ + a h + 1 = n F a 1 ( x ) F a 2 ( x ) ⋯ F a h + 1 ( x ) = 1 h ! · ∑ j = 1 h ( − 1 ) h − j · S ( h , j ) x 2 h − j × ∑ i = 0 n ( n − i + j ) ! ( n − i ) ! · 2 h + i − j − 1 i · ( − 1 ) i · 2 i · F n − i + j ( x ) x i ,$
where $S ( h , i )$ is a second order non-linear recurrence sequence defined by $S ( h , 0 ) = 0$, $S ( h , h ) = 1$, and $S ( h + 1 , i + 1 ) = 2 · ( 2 h − 1 − i ) · S ( h , i + 1 ) + S ( h , i )$ for all positive integers $1 ≤ i ≤ h − 1$.
In particular, taking $n = 0$ and $x = 1$, we can also deduce the following corollaries from Theorem 1.
Corollary 1.
For any positive integer $h ≥ 1$, we have the identity:
$∑ j = 1 h ( − 1 ) h − j · S ( h , j ) · j ! · x j · F j ( x ) = h ! · x 2 h .$
Corollary 2.
For any positive integer $h ≥ 1$, we have the identity:
$∑ j = 1 h ( − 1 ) h − j · S ( h , j ) · j ! · F j + 1 = h ! .$
The formula in Corollary 1 profoundly reveals the close relationship among the Fibonacci polynomials. Taking $h = 2$, then from Theorem 1, we can also infer the following:
Corollary 3.
For any integer $n ≥ 0$, we obtain:
$∑ a + b + c = n F a + 1 · F b + 1 · F c + 1 = 1 2 ∑ i = 0 n ( − 1 ) i 2 i ( n + 1 − i ) ( n + 2 − i ) ( i + 1 ) · F n + 3 − i − ∑ i = 0 n ( − 1 ) i 2 i ( n + 1 − i ) ( i + 1 ) ( i + 2 ) · F n + 2 − i .$
To further comprehend the properties of the sequence $S ( h , i )$, here we give first several terms of $S ( h , i )$ in the following Table 1:
By observing this table, we can easily find that for primes $p = 2 , 3 , 5 , 7$, we have the congruences $S ( p , i ) ≡ 0 mod p ( p − 1 )$ for $0 ≤ i ≤ p − 1$. In fact, this conclusion is also correct for all primes p. That is, we obtain the following:
Theorem 2.
Let p be a prime. Then, for any integer i with $1 ≤ i ≤ p − 1$, we acquire the congruence:
$S ( p , i ) ≡ 0 mod p ( p − 1 ) .$

## 2. Several Simple Lemmas

In this part, we will give several necessary lemmas in the proof process of our theorems. First of all, we have the following:
Lemma 1.
Let function $f ( t ) = 1 1 − x t − t 2$. Then, for any positive integer n and real numbers x and t with $| 2 t | < | x |$, we have the identity:
$n ! · f n + 1 ( t ) = ∑ i = 1 n ( − 1 ) n − i · S ( n , i ) · f ( i ) ( t ) x + 2 t 2 n − i ,$
where $S ( n , i )$ is defined in the theorem and $f ( h ) ( t )$ indicates the h-order derivative of $f ( t )$ with respect to variable t.
Proof.
In fact, we can prove this Lemma 1 by mathematical induction. By the properties of the derivative, we have:
$f ′ ( t ) = ( x + 2 t ) · 1 − x t − t 2 − 2 = ( x + 2 t ) · f 2 ( t )$
or:
$f 2 ( t ) = f ′ ( t ) x + 2 t = S ( 1 , 1 ) · f ′ ( t ) x + 2 t .$
That is, Lemma 1 is true for $n = 1$. Assuming Lemma 1 holds for $1 ≤ n = h$, we have,
$h ! · f h + 1 ( t ) = ∑ i = 1 h ( − 1 ) h − i · S ( h , i ) · f ( i ) ( t ) x + 2 t 2 h − i .$
Next, from (3) and the definitions of $S ( k , i )$ and the derivative, we obtain:
$( h + 1 ) ! · f h ( t ) · f ′ ( t ) = ( h + 1 ) ! · ( x + 2 t ) · f h + 2 ( t ) = ∑ i = 1 h ( − 1 ) h − i + 1 2 ( 2 h − i ) · S ( h , i ) x + 2 t 2 h + 1 − i · f ( i ) ( t ) + ∑ i = 1 h ( − 1 ) h − i · S ( h , i ) x + 2 t 2 h − i · f ( i + 1 ) ( t ) = ( − 1 ) h 2 ( 2 h − 1 ) S ( h , 1 ) x + 2 t 2 h · f ′ ( t ) + ∑ i = 1 h − 1 ( − 1 ) h − i 2 ( 2 h − 1 − i ) S ( h , i + 1 ) x + 2 t 2 h − i · f ( i + 1 ) ( t ) + S ( h , h ) x + 2 t h · f ( h + 1 ) ( t ) + ∑ i = 1 h − 1 ( − 1 ) h − i · S ( h , i ) x + 2 t 2 h − i · f ( i + 1 ) ( t ) = ( − 1 ) h 2 ( 2 h − 1 ) S ( h , 1 ) x + 2 t 2 h · f ′ ( t ) + S ( h , h ) x + 2 t h · f ( h + 1 ) ( t ) + ∑ i = 1 h − 1 ( − 1 ) h − i 2 ( 2 h − 1 − i ) S ( h , i + 1 ) x + 2 t 2 h − i · f ( i + 1 ) ( t ) + ∑ i = 1 h − 1 ( − 1 ) h − i · S ( h , i ) x + 2 t 2 h − i · f ( i + 1 ) ( t ) = ( − 1 ) h · S ( h + 1 , 1 ) x + 2 t 2 h · f ′ ( t ) + S ( h + 1 , h + 1 ) x + 2 t h · f ( h + 1 ) ( t ) + ∑ i = 1 h − 1 ( − 1 ) h − i · S ( h + 1 , i + 1 ) x + 2 t 2 h − i · f ( i + 1 ) ( t ) = ( − 1 ) h · S ( h + 1 , 1 ) x + 2 t 2 h · f ′ ( t ) + S ( h + 1 , h + 1 ) x + 2 t h · f ( h + 1 ) ( t ) + ∑ i = 2 h ( − 1 ) h + 1 − i S ( h + 1 , i ) x + 2 t 2 h + 1 − i · f ( i ) ( t ) = ∑ i = 1 h + 1 ( − 1 ) h + 1 − i · S ( h + 1 , i ) · f ( i ) ( t ) x + 2 t 2 h + 1 − i .$
Thus, from (4), we deduce that:
$( h + 1 ) ! · ( x + 2 t ) · f h + 2 ( t ) = ∑ i = 1 h + 1 ( − 1 ) h + 1 − i · S ( h + 1 , i ) · f ( i ) ( t ) x + 2 t 2 h + 1 − i$
or:
$( h + 1 ) ! · f h + 2 ( t ) = ∑ i = 1 h + 1 ( − 1 ) h + 1 − i · S ( h + 1 , i ) · f ( i ) ( t ) x + 2 t 2 h + 2 − i .$
That is to say, Lemma 1 also applies for $n = h + 1$.
Now, Lemma 1 follows from the mathematical induction. ☐
Lemma 2.
For any positive integers h and k, we have the power series expansion:
$f ( h ) ( t ) ( x + 2 t ) k = 1 x k ∑ n = 0 ∞ ∑ i = 0 n ( n − i + h ) ! ( n − i ) ! · ( − 1 ) i · 2 i · F n − i + h ( x ) x i · i + k − 1 i t n ,$
where t and x are any real numbers with $| t | < | x |$.
Proof.
In fact, from the definition of the Fibonacci polynomials $F n ( x )$, we have:
$f ( t ) = 1 1 − x t − t 2 = ∑ n = 0 ∞ F n ( x ) · t n .$
For any positive integer h, from the properties of the power series, we can obtain:
$f ( h ) ( t ) = ∑ n = 0 ∞ ( n + h ) ( n + h − 1 ) ⋯ ( n + 1 ) · F n + h ( x ) · t n = ∑ n = 0 ∞ ( n + h ) ! n ! · F n + h ( x ) · t n .$
Let k be a positive integer. Then, for all real t and x with $| 2 t | < | x |$, noting that the power series expansion:
$1 x + 2 t = 1 x · ∑ n = 0 ∞ ( − 1 ) n · ( 2 t ) n x n ,$
we have:
$1 ( x + 2 t ) k = 1 x k · ∑ n = 0 ∞ ( − 1 ) n · n + k − 1 n · ( 2 t ) n x n .$
Applying (5), (6), and the multiplicative properties of the power series, we have:
$f ( h ) ( t ) ( x + 2 t ) k = 1 x k · ∑ n = 0 ∞ ( n + h ) ! n ! · F n + h ( x ) · t n ∑ n = 0 ∞ ( − 1 ) n n + k − 1 n · ( 2 t ) n x n = 1 x k ∑ n = 0 ∞ ∑ i + j = n ( j + h ) ! j ! · F j + h ( x ) · ( − 1 ) i · i + k − 1 i · 2 i x i t n = 1 x k ∑ n = 0 ∞ ∑ i = 0 n ( n − i + h ) ! ( n − i ) ! · F n − i + h ( x ) · ( − 1 ) i · i + k − 1 i · 2 i x i t n .$
This proves Lemma 2. ☐

## 3. Proofs of the Theorems

In this section, the proofs of our theorems will be completed. Firstly, we prove Theorem 1. For any positive integer h, from (1), Lemma 1, the definition of $f ( t )$, and the properties of the power series, we have:
$h ! · f h + 1 ( t ) = h ! · ∑ n = 0 ∞ F n ( x ) · t n h + 1 = h ! · ∑ n = 0 ∞ ∑ a 1 + a 2 + ⋯ + a h + 1 = n F a 1 ( x ) F a 2 ( x ) ⋯ F a h + 1 ( x ) · t n .$
On the other hand, applying Lemma 2, we also have:
$h ! · f h + 1 ( t ) = ∑ j = 1 h ( − 1 ) h − j · S ( h , j ) · f ( j ) ( t ) x + 2 t 2 h − j = ∑ j = 1 h ( − 1 ) h − j S ( h , j ) x 2 h − j × ∑ n = 0 ∞ ∑ i = 0 n ( n − i + j ) ! ( n − i ) ! · F n − i + j ( x ) · 2 h + i − j − 1 i · ( − 1 ) i · 2 i x i t n = ∑ n = 0 ∞ ∑ j = 1 h ( − 1 ) h − j · S ( h , j ) x 2 h − j ∑ i = 0 n ( n − i + j ) ! ( n − i ) ! · ( − 1 ) i · 2 i · F n − i + j ( x ) x i × 2 h + i − j − 1 i · t n .$
Combined with (7), (8), and Lemma 1 and compared with the coefficients of the power series, we may immediately deduce the identity:
$h ! ∑ a 1 + a 2 + ⋯ + a h + 1 = n F a 1 ( x ) F a 2 ( x ) F a 3 ( x ) ⋯ F a h ( x ) · F a h + 1 ( x ) = ∑ j = 1 h ( − 1 ) h − j · S ( h , j ) x 2 h − j ∑ i = 0 n ( n − i + j ) ! ( n − i ) ! · 2 h + i − j − 1 i ( − 1 ) i · 2 i · F n − i + j ( x ) x i .$
This proves Theorem 1.
Now, we use the mathematical induction to prove Theorem 2. Taking $h = p$ in Corollary 1, we have:
$∑ j = 1 p ( − 1 ) p − j · S ( p , j ) · j ! · x j · F j ( x ) = p ! · x 2 p$
or from (1), we have:
$∑ j = 1 p − 1 ( − 1 ) p − j · S ( p , j ) · j ! · x j · F j ( x ) = − p ! · ∑ k = 1 p − 1 2 ( p − k ) ! k ! · ( p − 2 k ) ! · x 2 p − 2 k .$
For convenience, we let:
$W ( x ) = ∑ j = 1 p − 1 ( − 1 ) p − j · S ( p , j ) · j ! · x j · F j ( x )$
and:
$H ( x ) = − p ! · ∑ k = 1 p − 1 2 ( p − k ) ! k ! · ( p − 2 k ) ! · x 2 p − 2 k .$
Then, from the definition of the derivative, we have:
$W ( 2 p − 2 ) ( 0 ) = − S ( p , p − 1 ) · ( p − 1 ) ! · ( 2 p − 2 ) !$
and:
$H ( 2 p − 2 ) ( 0 ) = − p ! · ( p − 1 ) · ( 2 p − 2 ) ! .$
Combining (9), (10), and (11), we have:
$S ( p , p − 1 ) = p ( p − 1 ) ≡ 0 mod p ( p − 1 ) .$
That is, Theorem 2 is true for $i = p − 1$.
Suppose that Theorem 2 is true for all integers $1 < h ≤ i ≤ p − 1$. That is,
$S ( p , i ) ≡ 0 mod p ( p − 1 ) , h ≤ i ≤ p − 1 .$
Now, we prove that Theorem 2 is also correct for integer $i = h − 1$. Let $H = min { p − 1 , 2 h − 2 }$. Then, note that:
$W ( 2 h − 2 ) ( 0 ) = ∑ j = h − 1 H ( − 1 ) p − j · S ( p , j ) · j ! · ( h − 1 ) ! · ( 2 h − 2 ) ! ( j + 1 − h ) ! · ( 2 h − 2 − j ) ! ,$
$H ( 2 h − 2 ) ( 0 ) = 0 if h < p + 3 2 , − p ! · ( h − 1 ) ! · ( 2 h − 2 ) ! ( p + 1 − h ) ! · ( 2 h − 2 − p ) ! if h ≥ p + 3 2$
and:
$W ( 2 h − 2 ) ( 0 ) = ∑ j = h − 1 H ( − 1 ) p − j · S ( p , j ) · j ! · ( h − 1 ) ! · ( 2 h − 2 ) ! ( j + 1 − h ) ! · ( 2 h − 2 − j ) ! = H ( 2 h − 2 ) ( 0 ) = 0 if h < p + 3 2 , − p ! · ( h − 1 ) ! · ( 2 h − 2 ) ! ( p + 1 − h ) ! · ( 2 h − 2 − p ) ! if h ≥ p + 3 2 .$
Combining (16) and the induction hypothesis (13), we can deduce that:
$S ( p , h − 1 ) ≡ 0 mod p ( p − 1 ) .$
That is to say, Theorem 2 is also correct for $i = h − 1$. Now, Theorem 2 follows from the mathematical induction.
This completes the proofs of all our theorems.

## 4. Conclusions

The main results of this paper are Theorems 1 and 2. The feature of Theorem 1 is to express the complex sums (2) as a simple combination of $F n ( x )$, and its right side is very easy to calculate. In addition, it also profoundly reveals the structural properties of the Fibonacci polynomials. That is, the convolution (2) is composed of $F i ( x )$ and some recursive sequences $S ( h , j )$. Actually, $S ( h , j )$ in Theorem 1 can be calculated immediately by computer, which is very practical and easy.
Theorem 2 proves interesting congruence properties of the sequence $S ( p , i )$. In particular, its proving method is also very unique, and the mathematical induction is used upside down. What surprised us is that $p ( p − 1 )$ divides $S ( p , i )$ for all $1 ≤ i ≤ p − 1$.

## Author Contributions

All authors have equally contributed to this work. All authors read and approved the final manuscript.

## Funding

This work is supported by the NSF (11771351) of P. R. China.

## Acknowledgments

The authors would like to thank the Editor and referees for their very helpful and detailed comments, which have significantly improved the presentation of this paper.

## Conflicts of Interest

The authors declare that there are no conflicts of interest regarding the publication of this paper.

## References

1. Yi, Y.; Zhang, W.P. Some identities involving the Fibonacci polynomials. Fibonacci Q. 2002, 40, 314–318. [Google Scholar]
2. Wu, Z.G.; Zhang, W.P. The sums of the reciprocals of Fibonacci polynomials and Lucas polynimials. J. Inequal. Appl. 2012, 2012, 134. [Google Scholar] [CrossRef]
3. Wu, Z.G.; Zhang, W.P. Several identities involving the Fibonacci polynomials and Lucas polynimials. J. Inequal. Appl. 2013, 2013, 205. [Google Scholar] [CrossRef]
4. Ye, X.L.; Zhang, Z.Z. A common generalization of convolved generalized Fibonacci and Lucas polynomials and its applications. Appl. Math. Comput. 2017, 306, 31–37. [Google Scholar] [CrossRef]
5. Kim, T.; Dolgy, D.V.; Kim, D.S. Representing sums of finite products of Chebyshev polynomials of the second kind and Fibonacci polynomials in terms of Chebyshev polynomials. Adv. Stud. Contemp. Math. 2018, 28, 321–336. [Google Scholar]
6. Chen, L.; Zhang, W.P. Chebyshev polynomials and their some interesting applications. Adv. Differ. Equ. 2017, 2017, 303. [Google Scholar]
7. Kitayama, H.; Shiomi, D. On the irreducibility of Fibonacci and Lucas polynomials over finite fields. Finite Fields Their Appl. 2017, 48, 420–429. [Google Scholar] [CrossRef]
8. Li, X.X. Some identities involving Chebyshev polynomials. Math. Probl. Eng. 2015, 2015. [Google Scholar] [CrossRef]
9. Wang, W.P.; Wang, H. Generalized Humbert polynomials via generalized Fibonacci polynomials. Appl. Math. Comput. 2017, 307, 204–216. [Google Scholar] [CrossRef]
10. Ma, Y.K.; Lv, X.X. Several identities involving the reciprocal sums of Chebyshev polynomials. Math. Probl. Eng. 2017, 2017, 4194579. [Google Scholar] [CrossRef]
11. Sahin, A. On the Q analogue of Fibonacci and Lucas matrices and Fibonacci polynomials. Util. Math. 2016, 100, 113–125. [Google Scholar]
12. Wang, T.T.; Zhang, H. Some identities involving the derivative of the first kind Chebyshev polynomials. Math. Probl. Eng. 2015. [Google Scholar] [CrossRef]
13. Slanina, P. Generalizations of Fibonacci polynomials and free linear groups. Linear Multilinear Algebra 2016, 64, 187–195. [Google Scholar] [CrossRef]
14. Kaygisiz, K.; Sahin, A. Determinantal and permanental representations of Fibonacci type numbers and polynomials. Rocky Mt. J. Math. 2016, 46, 227–242. [Google Scholar] [CrossRef]
15. Trucco, E. On Fibonacci polynomials and wandering domains. Bull. Lond. Math. Soc. 2015, 47, 663–674. [Google Scholar] [CrossRef]
16. Kim, T.; Dolgy, D.V.; Kim, D.S.; Seo, J.J. Convolved Fibonacci numbers and their applications. Ars Combin. 2017, 135, 119–131. [Google Scholar]
17. Kim, T.; Kim, D.S.; Dolgy, D.V.; Park, J.-W. Sums of finite products of Chebyshev polynomials of the second kind and of Fibonacci polynomials. J. Inequal. Appl. 2018, 148. [Google Scholar] [CrossRef] [PubMed]
18. Kim, T.; Kim, D.S.; Kwon, J.; Dolgy, D.V. Expressing Sums of Finite Products of Chebyshev Polynomials of the Second Kind and of Fibonacci Polynomials by Several Orthogonal Polynomials. Mathematics 2018, 6, 210. [Google Scholar] [CrossRef]
19. Zhang, Y.X.; Chen, Z.Y. A new identity involving the Chebyshev polynomials. Mathematics 2018, 6, 244. [Google Scholar] [CrossRef]
Table 1. Values of $S ( k , i )$.
Table 1. Values of $S ( k , i )$.
$S ( h , i )$$i = 1$$i = 2$$i = 3$$i = 4$$i = 5$$i = 6$$i = 7$$i = 8$
$h = 1$1
$h = 2$21
$h = 3$1261
$h = 4$12060121
$h = 5$1680840180201
$h = 6$30,24015,1203360420301
$h = 7$665,280332,64075,60010,080840421
$h = 8$17,297,2808,648,6401,995,840277,20025,2001512361